2022
DOI: 10.1039/d1tc05263b
|View full text |Cite
|
Sign up to set email alerts
|

Versatile methods for improving the mechanical properties of fullerene and non-fullerene bulk heterojunction layers to enable stretchable organic solar cells

Abstract: We develop and evaluate two methods aimed at enhancing the mechanical resistance and stretchability of bulk heterojunction active layers in organic solar cells while maintaining photovoltaic performance intact. These techniques...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…Some studies demonstrated that adding insulating polymers such as polystyrene-block-poly(ethylene-ran-butylene)block-polystyrene, polydimethylsiloxane, or poly(aryl ether) s to the active layer blend films can improve the extensibility of the films. [29][30][31][32] In addition, introducing polymerized small molecule acceptors such as PY-IT can effectively enhance ductility. [33,34] However, the regulation mechanism of stretchability of ternary blends is still poorly understood, especially other morphology-stretchability relationships under stretching.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that adding insulating polymers such as polystyrene-block-poly(ethylene-ran-butylene)block-polystyrene, polydimethylsiloxane, or poly(aryl ether) s to the active layer blend films can improve the extensibility of the films. [29][30][31][32] In addition, introducing polymerized small molecule acceptors such as PY-IT can effectively enhance ductility. [33,34] However, the regulation mechanism of stretchability of ternary blends is still poorly understood, especially other morphology-stretchability relationships under stretching.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the Anthopoulos group has shown that the chemical structure of the crosslinker plays an important role in determining the mechanical properties. [17] For example, Dauzon et al crosslinked fullerene acceptors in P3HT:PCBM bulk heterojunctions using three bisazide crosslinkers: 1,12-diazidododecane (C 12 N 3 ), 1,11-diazido-3,6,9-trioxaundecane (PEG 3 N 3 ), and poly(ethylene glycol) bisazide (PEG N N 3 ). [17] Increasing the crosslinker loading and increasing the carbon chain length of the crosslinker both resulted in a decrease in the elastic modulus.…”
Section: Introductionmentioning
confidence: 99%
“…[17] For example, Dauzon et al crosslinked fullerene acceptors in P3HT:PCBM bulk heterojunctions using three bisazide crosslinkers: 1,12-diazidododecane (C 12 N 3 ), 1,11-diazido-3,6,9-trioxaundecane (PEG 3 N 3 ), and poly(ethylene glycol) bisazide (PEG N N 3 ). [17] Increasing the crosslinker loading and increasing the carbon chain length of the crosslinker both resulted in a decrease in the elastic modulus. Encouragingly, the authors also showed that small loadings of crosslinker (5 wt%) could be incorporated in a P3HT:PCBM solar cell without reducing the power conversion efficiency (PCE).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of crystallinity enhancement of the crosslinked films is unclear but might be due to the functioning of 1-NIPS as nucleating agents or crosslinking-induced immobilization of alkyl chains. [60][61][62] Nucleating agents can promote the microstructure formation, i.e., crystallization, of conjugated polymers during the film forming process and the thermal annealing process. [60,63,64] Additional GIXD results for non-annealed DPPDTT/1-NIPS films provide the evidence that 1-NIPS promotes the crystallization of DPPDTT during thermal annealing process (Figure S29, Supporting Information).…”
Section: Effect Of Crystalline Structure On Crosslinking-induced Defo...mentioning
confidence: 99%